Essential Physical Medicine and Rehabilitation - Cooper, Grant.; Cooper, Grant. (Musculoskeletal Medicine,, 2006)
Every medical student and junior resident needs a basic introductory survey that concisely presents all of the critical information underlying their specialty. In Essential Physical Medicine and Rehabilitation, nationally and internationally recognized experts join forces to summarize the essential facts needed to do a successful clinical rotation in physical medicine and rehabilitation (PM&R). Writing to be quickly read and comprehended, the authors spell out the implications of brain injury, the effects of spinal cord injury, the uses of orthotics and prosthetics, and the crucial importance of cardiac and pulmonary rehabilitation to maximize functional independence. Additional chapters concisely detail the principles of pediatric, neuromuscular, cancer, and orthopedic rehabilitation, and demonstrate the use of electrodiagnostic techniques that can be used to help localize a lesion of the neuromuscular system and determine its severity, time course, and prognosis. Comprehensive in its organization and concise in its presentation of essential information, Essential Physical Medicine and Rehabilitation not only explains to the medical student and junior resident everything they need to know before and during residency training and a first rotation, but also provides a handy review for passing PM&R board exams.